Pilot study of archimedes virtual bronchoscopic navigation system-guided biopsy to diagnose lung nodules in children - Yang, Haiming; Turgon, Elijan; Pan, Yuena; Wen, Xiaohui; Zhang, Xiaoyan; Shen, Yuelin; Wang, Feng (Frontiers in Pediatrics, 2023)
BACKGROUND Peripheral Pulmonary Lesions are not uncommon in children, but there is currently a lack of an effective method to obtain a diagnostic lung biopsy without complications. RESEARCH QUESTION Is the Archimedes Virtual Bronchoscopic Navigation System safe and effective for the diagnosis of peripheral Pulmonary Lesions in children? STUDY DESIGN AND METHODS This study retrospectively analyzed the clinical manifestations, radiological characteristics, intra- and postoperative complications, and pathological results of five children who underwent Archimedes-guided biopsy of peripheral Pulmonary Lesions in XXXX from May 2021 to May 2022. RESULTS The cohort comprised five children (all males) with a disease-onset age of 7.1–15.8 years. A guide sheath was inserted through the bronchoscope under the guidance of Archimedes combined with radial endobronchial ultrasound to complete the biopsy under general anesthesia. The fused fluoroscopy technique was used to reconfirm the location of the forceps prior to biopsy in all children. The forceps reached the lesion under the guidance of the navigation and the samples were collected successfully in all children. Pathological examination of the biopsy specimens showed Epstein-Barr virus infection-related lymphoproliferative disease in one child, pulmonary metastasis of rhabdomyosarcoma in one child, and pulmonary vasculitis in one child; high-throughput sequencing of the biopsy tissue sample suggested Mycobacterium tuberculosis (sequence no. 80) in one child and Aspergillus (sequence no. 40) in another child. All five children tolerated the biopsy procedure without developing postoperative complications, such as pneumothorax and hemoptysis. Interpretation: Archimedes-guided bronchoscopic lung biopsy is a feasible and efficient way to diagnose peripheral pulmonary Lesions in children without causing complications.